(untitled) (Biological Sciences - PJSIR, 1999)
A laboratory spray column of variable height was used for the extraction of zinc from an aqueous sulphate solution by di (2-ethylhexyl) phosphoric acid (DEHPA) in n-heptane. Three sets of nozzles of different diameters were employed in order to change the Sauter mean diameter of the dispersed phase. Experiments covered a wide range of concentrations and flow rates. Experimental results were compared with predictions obtained by using the two design algorithms (one based on the interfacial chemical kinetics, the other on interfacial equilibrium). Results simulated with the kinetic model were in good agreement with experiments over the whole range of conditions investigated. the equilibrium model underestimated the column heights by factors ranging between 0.25 and 0.5.